Quantum Chemistry Study of 1,3-Diazaspiro[4,5/4]dec/non-1-en-4-one Derivatives - Wei, Qingli; Liu, Nian; Sheng Zhang, Shu; Li, Xue-Mei (Asian Journal of Chemistry, 2010)
The geometry structures of the title compounds were optimized by means of the selfconsistent ab initio restricted Hartree-Fock (RHF) level with 3-21G basis set. The quantitative structure-activity relationship of the title compounds was systematically investigated based on Hasch-Fujita approach. A correlative equation between IC50 and ELUMO, C log P and MR was well established. The correlation coefficient r is 0.9647 and pIC50 = 11.5137 - 116.9688ELUMO - 0.1959 C log P + 0.2820 MR n = 14, R = 0.9647, F = 44.69 shows that the introduction of electron-withdrawing groups on to the R2-position would be favourable to the activity of the compounds. C log P was influenced by the number of carbons on the spiro. Reducing of C log P and building up the polarization of the compounds would be favourable to the activity.